2022
DOI: 10.1007/s00421-022-05063-6
|View full text |Cite
|
Sign up to set email alerts
|

Knee position sense and knee flexor neuromuscular function are similarly altered after two submaximal eccentric bouts

Abstract: Purpose This study examined eccentric-induced fatigue effects on knee flexor (KF) neuromuscular function and on knee position sense. This design was repeated across two experimental sessions performed 1 week apart to investigate potential repeated bout effects. MethodsSixteen participants performed two submaximal bouts of KF unilateral eccentric contractions until reaching a 20% decrease in maximal voluntary isometric contraction force. Knee position sense was evaluated with position-matching tasks in seated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…8 Some studies reported that proprioception, such as position sense (PS), was impaired following eccentric exercise that induced muscle damage. [8][9][10][11] Only three studies have investigated the IL-RBE on proprioception. 8,10,11 For example, Paschalis et al 8 reported that changes in PS and joint reaction angle (JRA) after maximal eccentric exercise of the KF were significantly smaller and recovered faster after the second bout compared to the first bout that was performed by the same muscle 4 weeks earlier.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Some studies reported that proprioception, such as position sense (PS), was impaired following eccentric exercise that induced muscle damage. [8][9][10][11] Only three studies have investigated the IL-RBE on proprioception. 8,10,11 For example, Paschalis et al 8 reported that changes in PS and joint reaction angle (JRA) after maximal eccentric exercise of the KF were significantly smaller and recovered faster after the second bout compared to the first bout that was performed by the same muscle 4 weeks earlier.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Only three studies have investigated the IL-RBE on proprioception. 8,10,11 For example, Paschalis et al 8 reported that changes in PS and joint reaction angle (JRA) after maximal eccentric exercise of the KF were significantly smaller and recovered faster after the second bout compared to the first bout that was performed by the same muscle 4 weeks earlier. In contrast, Da Silva et al 11 found no significant difference in PS of knee joint between the first and second bouts of submaximal eccentric exercise of the same KF separated by 1 week.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations led the authors to suggest that the increase in position-matching errors following fatiguing eccentric protocols was due to exercise-induced alterations in the central nervous system [ 22 , 26 ]. Specifically, in a recent experiment, our group concurrently examined the effects of a submaximal fatiguing eccentric protocol of knee flexors (KF) on neuromuscular function and position sense at the knee using bilateral position-matching tasks [ 27 ]. During such tasks performed in seated position, errors increased in the presence of central fatigue immediately following the fatiguing eccentric protocol, but reverted to baseline levels 24 h post-exercise [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in a recent experiment, our group concurrently examined the effects of a submaximal fatiguing eccentric protocol of knee flexors (KF) on neuromuscular function and position sense at the knee using bilateral position-matching tasks [ 27 ]. During such tasks performed in seated position, errors increased in the presence of central fatigue immediately following the fatiguing eccentric protocol, but reverted to baseline levels 24 h post-exercise [ 27 ]. Acute eccentric-induced position sense alterations were attributed to disturbances in the integration and/or processing of positional signals at the somatosensory cortex level due to the actions from group III-IV afferents.…”
Section: Introductionmentioning
confidence: 99%